Heavily Indebted Poor Countries Initiative : List of Ring-Fenced Countries that Meet the Income and Indebtedness Criteria at end-2004. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper identifies the countries that meet the enhanced Heavily Indebted Poor Countries (HIPC) Initiative's income and indebtedness eligibility criteria based on end-2004 data. It also updates the status of these countries toward qualifying for debt relief and presents cost estimates of debt relief.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Kyrgyz Republic